2005
DOI: 10.1208/aapsj070246
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic parameter estimation: Population size versus number of samples

Abstract: The purpose of this study was to evaluate the effects of population size, number of samples per individual, and level of interindividual variability (IIV) on the accuracy and precision of pharmacodynamic (PD) parameter estimates. Response data were simulated from concentration input data for an inhibitory sigmoid drug efficacy (E(max)) model using Nonlinear Mixed Effect Modeling, version 5 (NONMEM). Seven designs were investigated using different concentration sampling windows ranging from 0 to 3 EC(50) (EC(50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
(16 reference statements)
1
16
1
Order By: Relevance
“…[11] Both the θ γ and ω γ 2 met the criteria for accuracy and precision at 100 (C max =0.84 EC 50 units) and 200 mg (C max =1.7 EC 50 units) with γ of 2, 100 to 400 mg (C max =0.84 to 3.4 EC 50 units) with γ of 5, and 200 mg (C max =1.7 EC 50 units) with γ of 10. On the other hand, Girgis et al found that all θ γ and ω γ 2 were biased and imprecise when the Hill coefficient was high (γ=6.22), 4 to 5 blood samples were gathered [10] and Pai et al also reported similar results from spare sampling design, when γ were 1 or 2.51. [11] These results suggest that dense sampling design may be essential to get accurate and precise estimates of θ γ and ω γ 2 .…”
Section: Transl Clin Pharmacolmentioning
confidence: 97%
See 4 more Smart Citations
“…[11] Both the θ γ and ω γ 2 met the criteria for accuracy and precision at 100 (C max =0.84 EC 50 units) and 200 mg (C max =1.7 EC 50 units) with γ of 2, 100 to 400 mg (C max =0.84 to 3.4 EC 50 units) with γ of 5, and 200 mg (C max =1.7 EC 50 units) with γ of 10. On the other hand, Girgis et al found that all θ γ and ω γ 2 were biased and imprecise when the Hill coefficient was high (γ=6.22), 4 to 5 blood samples were gathered [10] and Pai et al also reported similar results from spare sampling design, when γ were 1 or 2.51. [11] These results suggest that dense sampling design may be essential to get accurate and precise estimates of θ γ and ω γ 2 .…”
Section: Transl Clin Pharmacolmentioning
confidence: 97%
“…Simulated concentrations were normalized by true EC 50 (=1000 ng/mL) to identify the generalized exposure-response relationship and then "EC 50 " was used as a unit to express normalized concentrations. [10,11] To evaluate the estimation performance for PD parameters at each dosing scenario, the median values and ranges of normalized maximum concentration (C max ) (normalized by EC 50 ) for single-dose study and normalized steady-state minimum concentration (C min,ss ) and C max,ss for multiple-dose study at each dose level at all values of γ were obtained using individual predicted values, which were calculated from the parameter estimates from 100 simulated subjects and the simulation time points in each scenario.…”
Section: Pk/pd Simulation and Estimationmentioning
confidence: 99%
See 3 more Smart Citations